A potential threat to amphibians in the European Natura 2000 network: Forecasting the distribution of the American bullfrog Lithobates catesbeianus. - Johovica, Iva (2020)
Freshwater biodiversity is declining at an accelerated pace. Climate change and associated global warming and changes in precipitation patterns, combined with the expansion of generalist -invasive species are two of the main threats. Niche-based models (NBMs) are becoming inevitable tools in invasive species risk assessment and in conservation decision-making. Lithobates catesbeianus is an invasive species globally known for its adverse ecological impacts on native amphibians and biodiversity. To assess species current and future climatic suitable areas at the global and European scales we used an ensemble forecasting approach. We considered six climatic variables, three timeframes (current, 2050, and 2070), and two CO2 emission scenarios. Temperature seasonality, minimum temperature of the coldest month, maximum temperature of the warmest month, and precipitation in the driest month were the most important variables predicting bullfrog occurrence. Globally currently 3.8% of land area is suitable for bullfrog and an increase of up to 5.2% in 2070 is expected. Increase in suitable areas is expected at higher latitudes, especially in North America and central Europe. Currently, 3.45% of total Natura 2000 area is suitable, and a predicted range gain of up to 355.93% (12.28%) is expected in the highest concentration scenarios predictions. This can indicate that the 64 native amphibian species present in the Natura 2000 network could be at increased risk. The choice of Natura 2000 for a geographic detailed analysis of the possible effects on native amphibians is due to its importance for habitats and wildlife conservation. Identification of its invasion-susceptible areas will allow resource and management practices optimization.